Light and Color Navigation of the Siberian City: the Case of Novosibirsk - Vorozheikina, Vera (project baikal, 2020)
Siberian cities with cold climates, short daylight hours and specific features of local traditional culture, such as Novosibirsk, need improvement of light and color navigation at night time. It is best to use light projection to improve pedestrian orientation. The projection of orienting symbols on horizontal and vertical surfaces will allow not only to indicate the way, but also to create a positive mood even on a short winter day. Given the existing interest in designing a smart city, managing the color navigation system from a personal gadget is also a novelty in the study.